Crafting and executing strategy : text and readings - Thompson, Arthur A., 1940-; Strickland, A. J. (Alonzo J.); Gamble, John (John E.) (Boston : McGraw-Hill/Irwin, 2007)
Presenting research findings from literature, this book incorporates the strategic practices of various companies, including 21 readings from noted business writers.
Includes bibliographical references and indexes.
Keywords: Strategic planning; Business planning